Sweetness of Gitanjali - Rahmatullah Hakimi (Randwick International of Education and Linguistics Science Journal, 2021)
Literal language talks in a higher level than common language, everyone doesn’t have the ability to speak on literal language. There is a question that how to speak on uncommonly speaking, this uncommon speaking is the highest quality of art. These quality percepts the aesthetic of literature by the reader and Gitanjali is its best example. This master piece is an advice and enjoy. Here are devoted songs which show close relationship between lover and beloved, pain of separation with enjoyment, emotion and clear senses are interpreted with imaginative language, not only individuals but also the whole human being can see their pure love. This master piece of work has attractiveness and artistic. We will discuss both of them here.